Visual enunciation, the modern moment - Bertrand, Denis (E|C, 2020)
Unlike the pronominal system of natural languages, the reflexive dimension of visual representation takes on very different forms throughout history. The "modern moment" in the history of subjectivity that Foucault describes in his analysis of “Las Meninas” by Diego Velázquez is precisely the moment in which the reflective dimension of representation becomes the place of an intense and unprecedented speculative investment.